Expression of epidermal growth factor receptor in advance stage nonkeratinizing nasopharyngeal carcinoma in West Sumatra, Indonesia - Rahman, Sukri; Subroto, Histawara; Budiman, Bestari J; Asri, Aswiyanti; Bachtiar, Hafni (Archive of Oncology, 2018)
Introduction: Nasopharyngeal carcinoma is a head and neck cancer with a unique geographic distribution. Indonesia is one of the countries with an intermediate incidence of nasopharyngeal carcinoma where 13,000 new cases are found every year or 6.2 cases/100,000 in population per year. The subcellular mechanism of the nasopharyngeal carcinoma has not been clearly confirmed, but in several studies overexpression of the epidermal growth factor receptor was found. Based on histopathological classification, nonkeratinizing subtypes consisting of differentiated (WHO II) and undifferentiated (WHO III) are the most frequent types in endemic areas, whereas in non-endemic areas the majority of cases are keratinizing subtype (WHO I). The objective of this study was to evaluate the expression of epidermal growth factor receptor in advanced stage nonkeratinizing nasopharyngeal carcinoma as well as to evaluate difference in the expression between differentiated nonkeratinizing (WHO II) and undifferentiated (WHO III) nasopharyngeal carcinoma that may affect the anti-epidermal growth factor receptor therapy for nasopharyngeal carcinoma. Methods: Biopsies from 34 advance stage (stage III and stage IV) nonkeratinizing nasopharyngeal carcinoma consisting of 17 differentiated nonkeratinizing and 17 undifferentiated carcinomas were included in the study. Expression of epidermal growth factor receptor in tumor tissues was investigated by immunohistochemistry (IHC). Results: Our results demonstrated that epidermal growth factor receptor was expressed in 23 out of 34 subjects (67.65%). Expression in differentiated nonkeratinizing nasopharyngeal carcinoma was 76.47% (13 out of 17), and it was higher than in undifferentiated carcinoma (58.82%), but there was no statistically significant difference between the two histopathological subtypes (p=0.465). Conclusions: The epidermal growth factor receptor was expressed in most cases of advance stage nonkeratinizing nasopharyngeal carcinoma, and there was no difference in the expression between differentiated nonkeratinizing (WHO II) and undifferentiated nonkeratinizing nasopharyngeal carcinoma (WHO III).